Peran dan Manfaat Modal Sosial dalam Peningkatan Efektivitas Kerja Karyawan Sektor Usaha Mikro Kecil dan Menengah di Sentra Kerajinan Tas dan Koper Tanggulangin Sidoarjo: The Role and Benefits of Social Capital in Increasing the Work Effectiveness of Employees in the Micro, Small and Medium Enterprises Sector at the Tanggulangin Bag and Luggage Craft Center, Sidoarjo - Widodo, Harge Trio (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this research is to identify and describe the shape of social capital that exist in the centers of craft bags and suitcases Tanggulangin. Identify the role of social capital in improve the effectiveness of employees in the center of bags and suitcases craft Tanggulangin. Identify the use of social capital by craftmen in their business development. Sampling method used in this study are done by purposive, decide the informant by selective informant. Data analysis method used is descriptive analysis. The result showed that social capital is formed in the industrial centers of bags and suitcases Tanggulangin started from family, relatives, neighbors and their friends, and grow together with local habit. The role of social capital to form a network, a sense of trust, social norms, leadership, and solidarity among employees and craftsmen in Tanggulangin. The benefits of social capital in the industrial centers of bags and suitcases in Tanggulangin found to form a good mutual cooperation among them, the knowledge transfer, and maintained good communication. Efforts to increase social capital is done by sharing the workload and remuneration managed transparently and in accordance with the capabilities and contributions of employees.